A framework to evaluate the energy-environment-economic impacts of developing rooftop photovoltaics integrated with electric vehicles at city level. (November 2022) - Liu, Junling; Li, Mengyue; Xue, Liya; Kobashi, Takuro
Abstract: Building a smart energy system to promote photovoltaic (PV) utilization has become an important task for cities to achieve a low-carbon future. With a focus on the rooftop PV integrated with the electric vehicle (EV) system (PV + EV), this study developed a framework to simulate the interaction between the PV + EV systems and load and evaluate the energy–environment–economic influences at the city level. Shenzhen, China, was used as a case study. The results showed that with EVs batteries providing storage service to PV, PV self-consumption can be significantly improved from 78% in the PV only system to 95% in the PV + EV system by 2030. The system can supply 37% of the total power demand in Shenzhen, which is double the current electricity generation capacity. With reduced grid power consumption and oil combustion in vehicles, citywide CO2 emissions can be reduced by 42%. Avoided expenditures on fuel and electricity outweigh the additional capital investment of PV and EVs, leading to a total net cost savings of 21%. Compared to the PV system alone, the PV + EV system could provide more comprehensive benefits for Shenzhen. The analytical framework is generalizable to most cities in China and abroad that have yet to experience an increase in EV uptake.